Basic fibroblast growth factor‐treated adipose tissue‐derived mesenchymal stem cell infusion to ameliorate liver cirrhosis via paracrine hepatocyte growth factor. Issue 6 (June 2015) - Tang, Wei‐Ping; Akahoshi, Tomohiko; Piao, Jing‐Shu; Narahara, Sayoko; Murata, Masaharu; Kawano, Takahito; Hamano, Nobuhito; Ikeda, Tetsuo; Hashizume, Makoto
Abstract Background and Aim Recent studies show that adipose tissue‐derived mesenchymal stem cells have potential clinical applications. However, the mechanism has not been fully elucidated yet. Here, we investigated the effect of basic fibroblast growth factor‐treated adipose tissue‐derived mesenchymal stem cells infusion on a liver fibrosis rat model and elucidated the underlying mechanism. Methods Adipose tissue‐derived mesenchymal stem cells were infused into carbon tetrachloride‐induced hepatic fibrosis rats through caudal vein. Liver functions and pathological changes were assessed. A co‐culture model was used to clarify the potential mechanism. Results Basic fibroblast growth factor treatment markedly improved the proliferation, differentiation, and hepatocyte growth factor expression ability of adipose tissue‐derived mesenchymal stem cells. Although adipose tissue‐derived mesenchymal stem cells infusion alone slightly ameliorated liver functions and suppressed fibrosis progression, basic fibroblast growth factor‐treatment significantly enhanced the therapeutic effect in association with elevated hepatocyte growth factor expression. Moreover, double immunofluorescence staining confirmed that the infused cells located in fibrosis area. Furthermore, co‐culture with adipose tissue‐derived mesenchymal stem cell led to induction of hepatic stellate cell apoptosis and enhanced hepatocyte proliferation. However, these effects were significantly weakened by knockdown of hepatocyte growth factor. Mechanism investigation revealed that co‐culture with adipose tissue‐derived mesenchymal stem cells activated c‐jun N‐terminal kinase‐p53 signaling in hepatic stellate cell and promoted apoptosis. Conclusions Basic fibroblast growth factor treatment enhanced the therapeutic effect of adipose tissue‐derived mesenchymal stem cells, and secretion of hepatocyte growth factor from adipose tissue‐derived mesenchymal stem cells plays a critical role in amelioration of liver injury and regression of fibrosis.